2016
DOI: 10.1158/1078-0432.ccr-16-0569
|View full text |Cite
|
Sign up to set email alerts
|

The Potent ALK Inhibitor Brigatinib (AP26113) Overcomes Mechanisms of Resistance to First- and Second-Generation ALK Inhibitors in Preclinical Models

Abstract: Purpose: Non-small cell lung cancers (NSCLCs) harboring ALK gene rearrangements (ALK þ ) typically become resistant to the first-generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitor (TKI) crizotinib through development of secondary resistance mutations in ALK or disease progression in the brain. Mutations that confer resistance to second-generation ALK TKIs ceritinib and alectinib have also been identified. Here, we report the structure and first comprehensive preclinical evaluation of the nex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
279
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(292 citation statements)
references
References 30 publications
10
279
1
2
Order By: Relevance
“…However, any differences among these drugs in their ability to suppress clinically relevant ALK mutations, including those that may not be dominant initially but could emerge later, are more likely to be reflected in PFS or duration of response. [12][13][14][15][16]21 In preclinical models, brigatinib had broader predicted mutation coverage, compared with ceritinib and alectinib. 21 Consistent with this observation, in the phase I/II trial of brigatinib, the median PFS of patients with advanced ALK-positive NSCLC who previously received crizotinib (most of whom received 180 mg per day, with or without lead-in at 90 mg) was recently reported as 12.9 months, across all doses tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, any differences among these drugs in their ability to suppress clinically relevant ALK mutations, including those that may not be dominant initially but could emerge later, are more likely to be reflected in PFS or duration of response. [12][13][14][15][16]21 In preclinical models, brigatinib had broader predicted mutation coverage, compared with ceritinib and alectinib. 21 Consistent with this observation, in the phase I/II trial of brigatinib, the median PFS of patients with advanced ALK-positive NSCLC who previously received crizotinib (most of whom received 180 mg per day, with or without lead-in at 90 mg) was recently reported as 12.9 months, across all doses tested.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16]21 In preclinical models, brigatinib had broader predicted mutation coverage, compared with ceritinib and alectinib. 21 Consistent with this observation, in the phase I/II trial of brigatinib, the median PFS of patients with advanced ALK-positive NSCLC who previously received crizotinib (most of whom received 180 mg per day, with or without lead-in at 90 mg) was recently reported as 12.9 months, across all doses tested. 22 This extended PFS, relative to ceritinib 12-14 and alectinib 15,16 results, is substantiated by the median PFS of .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the interim, brigatinib has received breakthrough therapy designation by the FDA for the treatment of crizotinib-resistant, ALK -rearranged NSCLC. Some preclinical studies of brigatinib suggest activity against the G1202R mutation in cell lines and mouse models (128, 130), and a confirmed response to brigatinib has been reported in a patient with G1202R-mutant NSCLC (129). However, G1202R has also been detected in 43% (3/7) of ALK -positive NSCLC biopsies post-brigatinib (78).…”
Section: Developing Strategies To Overcome Resistancementioning
confidence: 98%
“…Preclinical work showed that brigatinib was more potent and maintained activity against 17 secondary ALK mutations, with superior inhibitory activity compared to crizotinib, ceritinib, and alectinib [32]. The phase I/II trial showed an ORR of 72% in previously crizotinib-treated ALK -rearranged NSCLC patients with an intracranial response rate of 53% [33].…”
Section: Therapeutic Optionsmentioning
confidence: 99%